Modeling economic growth in contemporary Greece - Vlachos, Vasileios; Bitzenis, Aristidis; Sergi, Bruno S. (Bingley, U.K. : Emerald Publishing Limited, 2021)
In the aftermath of the devastating economic depression suffered for almost a decade, Modeling Economic Growth in Contemporary Greece assesses the conditions shaping the Greek economy's restart, discussing the effect of institutions on the business environment and highlighting the factors which are critical for achieving sustainable economic growth. The intrinsic properties of the Greek economic and business environment imply that there are country-specific factors responsible for the performance of the Greek economy, which is differentiated from its European counterparts. Despite being a member of the European Union since 1981 and one of the twelve first countries who adopted the euro, Greece has not been able to converge in crucial macroeconomic indicators with the early euro area Member States. The European stimulus package to support post COVID-19 recovery appears as a unique opportunity for Greece to develop a long-term vision and materialize reforms that will unlock the economy's true potential. This latest book in the Entrepreneurship and Global Economic Growth series is centred around the determinants of and obstacles to Greece's sustainable economic growth, presenting the macroeconomic and external environment and the dynamics of Greek economy and focuses onto internal conditions shaped by country-specific characteristics affecting labor and product markets' efficiency and the performance of institutions and production factors.
Foreword / Apostolos Serletis -- Chapter 1. Determinants of and obstacles to economic growth in contemporary greece / Vasileios Vlachos, Aristidis Bitzenis, and Bruno S. Sergi Part 1 - Dynamics of the Greek economy -- Chapter 2. Competitive position and dynamics of the greek economy / Vasileios Vlachos and Aristidis Bitzenis -- Chapter 3. An odyssey with a happy end? Growth challenges, successes and failures of greece during covid-19 era / Konstantinos J. Hazakis -- Chapter 4. Forecasting greek real GDP based on arima modeling / Chaido Dritsaki and Melina Dritsaki -- Chapter 5. Nominal or real convergence with the emu criteria: The case of greece / Aristidis Bitzenis and Pyrros Papadimitriou Part 2 - Policies, Institutions, and Markets -- Chapter 6. The interactions between governance quality and economic development / Chara Vavoura, Dimitris Manolopoulos, and Ioannis Vavouras -- Chapter 7. Social policy in dribs and drabs for the greek crisis / Dimitris Venieris -- Chapter 8. The greek labour market during the crisis: New evidence on the evolution of wages, employment and unemployment / Evangelia Papapetrou and Pinelopi Tsalaporta -- Chapter 9. Sme productivity in greece: The role of human capital, ict adoption and innovation / Ioannis Giotopoulos, Pelagia Kontaxaki, and Helen Louri -- Chapter 10. The impact of competition law on the greek economy / Mark Clough QC and Efthymios Bourtzalas Part 3 - Characteristics and performance of selected industries -- Chapter 11. Greek banking system during the crisis and beyond / Fotios Pasiouras and Minas-Polyvios Tsagkarakis -- Chapter 12. The agri-food sector in greece: Prospects and possibilities / Stathis Klonaris -- Chapter 13. Energy resources, local content policies and economic growth: The case of hydrocarbon exploration in greece / Stella Tsani -- Chapter 14. The importance of tourism for the greek economy: Traits and development / Iordanis Katemliadis and Andreas Papatheodorou -- Chapter 15. The greek ict sector a
Includes index.
Print version record.
Keywords: Economic development -- Greece; Business & Economics -- Development -- Economic Development; Development economics & emerging economies